Contribution of international ecotourism to comprehensive economic development and convergence in the Central American and Caribbean region. Issue 33 (15th July 2018) - Gunter, Ulrich; Ceddia, M. Graziano; Leonard, David; Tröster, Bernhard
ABSTRACT: Drawing on the positive experience from Costa Rica, the study examines whether international ecotourism makes a significant contribution to comprehensive economic development for the Central American and Caribbean region and contributes to comprehensive economic convergence. Following a standard empirical growth model, a dynamic panel regression model is estimated using time-series data from 1995 until 2012 for a cross section of seven countries. The interaction of international tourism and various established sustainability indicators is employed allowing ecotourism to be consistently quantified across countries, while numerous country-specific structural characteristics are controlled for. The estimation results show that international ecotourism has a statistically significant positive effect on both traditional economic development (real GDP per capita) and comprehensive economic development (adjusted net savings; ANS per capita), which is a measure of a society's potential future well-being, thus providing evidence in support of the tourism-led growth hypothesis and pointing towards an important role for ecotourism in driving comprehensive economic convergence.